Study on the management of accounts receivable and influence on liquidity - Latorre Asmad, Mónica Rubí (2021)
The main objective of this research was to validate the role of accounts receivable and demonstrate the influence that the liquidity it provides within the profitability of the company has on the participation of the principals of the Accounting area (10) between executives and technicians of the company under study. A descriptive correlational study was done. The results obtained are that there is a direct correlation between accounts receivable and liquidity in which it is emphasized that both variables are directly related to the purpose of the company obtaining profitability and continuing to grow within the business environment.